CATCH OF BLUE SWIMMING CRAB DURING BRIGHT AND DARK MOON PHASE WITH COLLAPSIBLE POT AT OESAPA WATERS, KUPANG CITY - Tallo, Ismawan; Boikh, Lebrina Ivantry; Yahyah (Departemen PSP IPB, 2025)
The blue swimming crabs in the waters of Oesapa, Kupang City are caught using collapsible pots during both the bright moon and dark moon phases. These fishing activities influence the quantity and size of the catch. The study aimed to compare the quantity and carapace-wide size of blue swimming crab (Portunus pelagicus Linnaeus, 1758) caught using several collapsible pots during the bright moon phase and the dark moon phase in the waters of Oesapa, Kupang City. The research was conducted from October 17th-22nd, 2024 (bright moon phase), and November 1st-5th, 2024 (dark moon phase). The tools and materials used in the study included 30 collapsible pots measuring 60 cm x 42 cm x 20 cm (L x W x H) baited with slipmouth fish (Leiognathus equulus). The pots were deployed in the water using the longline method and left for 24 hours. The number of crabs caught was recorded, and the carapace width of each crab was measured. The data were quantitatively analyzed using descriptive methods. The results showed that the average number of blue swimming crabs caught during the bright moon phase was eight individuals, while during the dark moon phase only 2.75 or three individuals. The average carapace width of crabs caught with the collapsible pot in Oesapa waters during the bright moon phase was 11.26 cm, whereas it was 11.93 cm in the dark moon phase. This difference showed that crabs caught varying numbers and sizes of carapace widths during the bright and dark moon phases. Key words: collapsible pot, moon phase, Oesapa waters, blue swimmer crab